A negative residual stress gradient based micro bridge mechanism for on-chip lifting of micro structures. (26th April 2010) - Chang, J.S.; He, S.
In this paper, a micro bridge mechanism is presented for on-chip lifting of micro structures. The micro bridge mechanism is made of the thin film with negative residual stress gradient across the thickness. It can be used for constructing vertically moving micro devices or calibrating the residual stress in micro fabricated thin films. The principle of the micro bridge mechanism is explained. An approximation model is developed to estimate the lifting height of the bridge mechanism. Prototypes with various dimensions are fabricated using the MetalMUMPs process and were experimentally measured. Experimental measurements show that even being limited by silicon nitride beams, a lifting height of 30-50 μm has been achieved by the micro bridge mechanism.